Assessment on factors affecting adoption and total income from vermicompost production in Chitwan, Nepal - Devkota, D.; Dhakal, S. C.; Dhakal, D.; Dhakal, D. D.; Ojha, R. B. (Journal of the Institute of Agriculture and Animal Science, 2018)
Vermicompost production technology uses half decomposed organic wastes to feed earthworms which produces nutrient enriched compost. Vermicompost production supports both organic waste management as well as organic farming. A research was conducted with the aim to assess the production and marketing aspect of vermicompost in Chitwan district during the year 2013. Interview schedule was used to collect information from all the 32 vermicompost producers within the study area and 32 adjacent non-producers were selected through snowball sampling. The total respondents' size was 64. The non-producers were farmers with few of them vermicompost users. Training on vermicompost production, group membership and type of farming were the significant factors affecting adoption of vermicompost production technology whereas the volume of earthworm reared and labor use were the significant factors affecting total income from vermicompost production. Resource use efficiency revealed that volume of earthworm reared and material cost were being over utilized but the labor use was underutilized. The volume of earthworm reared and labor use was to be increased by 300 % and 1.48 % respectively to obtain optimum economic advantage. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page:19-26